PROBLEMATIKA DI AKHIR KEHIDUPAN PASIEN DEMENSIA BERAT - Diatri Lastri Nari* (Neurona Majalah Kedokteran Neuro Sains, 2018)
NUMBER OF PEOPLE LIVING WITH DEMENTIA WORLDWIDE IN 2015 WAS ESTIMATED AT 4747 MILLION REACHING 7563 MILLION IN 2030 DEMENTIA COULD CAUSE MANY ISSUES SUCH AS ESTABLISHING GOALS OF CARE FEEDING DIFFICULTY SWALLOWING DIFFICULTY DEHYDRATION PNEUMONIA AND DECISION MAKING WHEN THE PATIENT CANNOT ACTIVELY PARTICIPATE GOALS OF CARE FOR PATIENT WITH SEVERE DEMENTIA ARE PERSONCENTERED